2018
DOI: 10.1021/acs.iecr.7b04557
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Free Coating of Epoxysilicones for the Fabrication of Composite Membranes

Abstract: Solventless coated epoxysilicone composite membranes have been prepared from a UV curable epoxysilicone polymer for organic solvent nanoltration. Coatings were conducted solventless on a roll-to-roll pilot line using a forward gravure coating technique, and applied on a polyacrylonitrile or crosslinked polyetherimide support. Crosslinking of the polyetherimide support membrane with propanediamine enhanced the adhesion properties of the epoxysilicone selective layer. Penetration of the coating solution into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…S3 and Section S3, ESI †). [28][29][30][31][32] Performance of the fabricated membranes was investigated using a crossflow system with pure water and 2EH flowing counter-currently at 1.0 L min À1 (0.16 m s À1 ) ( Fig. S4, ESI †).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S3 and Section S3, ESI †). [28][29][30][31][32] Performance of the fabricated membranes was investigated using a crossflow system with pure water and 2EH flowing counter-currently at 1.0 L min À1 (0.16 m s À1 ) ( Fig. S4, ESI †).…”
Section: Resultsmentioning
confidence: 99%
“…(g) Threshold (phase breakthrough) pressures of the ÂSPAES membrane were measured with a dead-end filtration apparatus separately for each solvent with nitrogen gas (Section S3, ESI †). [28][29][30][31][32]…”
Section: Resultsmentioning
confidence: 99%
“…Poly[(3,3,3‐trifluoropropyl)methylsiloxane] PV membrane prepared with water as solvent exhibited a high membrane flux and furfural separation factor 50 . PDMS PV membranes could be prepared with a solventless procedure under UV radiation 51,52 . PDMS/ZSM‐5 composite membranes prepared via solvent‐free twin‐screw compounding and molding method showed a high PSI for pervaporation separation of ethanol aqueous solution 53 .…”
Section: Resultsmentioning
confidence: 99%
“…50 PDMS PV membranes could be prepared with a solventless procedure under UV radiation. 51,52 PDMS/ZSM-5 composite membranes prepared via solvent-free twin-screw compounding and molding method showed a high PSI for pervaporation separation of ethanol aqueous solution. 53 These new procedures allow for fast, green, and continuous fabrication of separation membranes for industrial applications.…”
Section: Comparison To Other Studiesmentioning
confidence: 99%
“…13,27 This permeance also surpasses that of most recently reported membranes, such as AlO x /PIM-1, 28 cross-linked PVDF, 29 and epoxysilicone composite membranes. 30 To further demonstrate their potential application in non-polar solvents, the composite membranes were applied in n-hexane. It was found that the composite membrane had an increasing permeance for nhexane from 0.6 to 2.6 L m À2 h À1 bar À1 (Fig.…”
Section: Organic Solvent Nanoltration Performancementioning
confidence: 99%